Molecular Diagnosis of the Toll-like Receptor 4 Genes and its Relationship with the Levels of some Immunoglobulin’s and Cytokines among Infected Women with Trichomoniasis - Zahraa Zuhair Mohammed Al- Mamoori (Journal of Global Pharma Technology, 2018)
Trichomoniasis, simply, is a sexually transmitted disease typically asymptomatic in men and resulting in vaginitis with a copious, frothy discharge and itching in women, caused by Trichomonasvaginalis. The study was conducted in Babylon Province during the period from October 2017 to June 2018 in AL-Hilla Teaching Hospital and AL-Zahra Hospital, to diagnosis Trichomonasvaginalis and toll like receptor 4usingpolymerase chain reaction. The relationship of TLR4 receptor with levels of some immunoglobulin and cytokines was investigated by immunological method. A total of (125) blood and fluid vagina samples were taken from women aged between (15-45) Years. The results showed that the total infection percent of T. vaginalis at a rate of (13.6 %) in PCR technique. And the total of TLR4 at a rate of  (86.66%). The results revealed that a significant elevation (P<0.01) in serum concentration of pro inflammatory cytokines interleukin (4), and immunoglobulin E and A in T. vaginalis infection patients in compared to healthy control group. The result showed the association between IgE, IL4 and TLR4 receptor of patients.Keywords:  Genes; Immunoglobulin’s; Cytokines; Infected women.